Electromyographic parameters for treatment of pelvic floor disorders in pregnant and postpartum women: A review protocol. - Alethéa Cury Rabelo Leitão; Silvia Oliveira Ribeiro Lira; Elizabel de Souza Ramalho Viana (PLoS ONE)
Electromyography is a widely used instrument in clinical practice to evaluate and treat pelvic floor disorders in pregnant and postpartum women. The objective of this study is to analyze the scientific evidence on the electromyography parameters used for treatment of pelvic floor disorders in pregnant women in any gestational week and postpartum women up to 12 months after delivery. A systematic review of randomized controlled experimental studies (clinical trials) and quasi-experimental studies in English, Portuguese or Spanish, which used electromyography as an intervention for treatment of pelvic floor disorders in pregnant or postpartum women up to 12 months after delivery will be performed in online databases (Scopus, Medline, Pedro, Scielo and Pubmed),. Risk of bias assessment will be performed using Cochrane group tools. The Rob 2.0 tool will be used for experimental studies and the Robins-I tool for non-experimental studies. The protocol was registered in PROSPERO (no.433510). The quality of the evidence will be analyzed using the GRADE System Methodological Guide and the systematic review structure will be performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.